A study of capital adequacy framework for Islamic banks with reference to Indonesia - Haryono, Yono (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2011)
Due to its important role for banking industry, Basel II Capital Standards have been developed by Basel Committee on Banking Supervision (BCBS) with a conventional bank's perspective. The balance sheet underlying the Basel II Capital Standards belongs to a conventional bank whose stmcture completely differs from that of an Islamic banks. Conventional bank is essentially based on the debtor-creditor relationship between the depositors and the bank on one hand, and between the borrowers and the bank on the other. Meanwhile, Islamic banks. due to the existence of partnership modes of funding and financing and other various contracts either in the f01m of contract of exchange (Mu 'awadat), contract of Ijarah, etc, make the contractual relationship in Islamic banks can be in the form of partnership. investor and trader, as well as a buyer and seller relationship. Therefore, Islamic banks have different risk profile as compared to conventional banks. Realizing these differences. a number of institutions have tried to develop the capital adequacy standards for Islamic banks adopting Basel II approaches. The Accounting and Auditing Organization of Islamic Financial Institutions (AAOIFI) has recommended to exclude the risk sharing account deposit in capital. In a similar vein, Islamic Financial Service Board (IFSB) has taken efforts to develop capital adequacy requirements for Islamic banks based on the Basel II Standards. This study, therefore, will be conducted to assess whether the existing capital adequacy standards developed by BCBS, IFSB as well as the standards applied in Indonesia are suitable with the risk profile of Islan1ic banks. This study will be conducted mainly by descriptive and comparative study to identify and establish the strengths and weaknesses of the existing capital adequacy standards. Based on the study, there are some weaknesses of those capital adequacy framework. The result of the study is expected to be beneficial for the development of the capital adequacy framework for Islamic banks particularly in Indonesia and will add to the literature of Islamic banking.